(untitled) (Malden, Mass., 1998)
Agriculture in the Tropics is one of the most successful and widely read books in the Tropical Agriculture Series and offers a general account of all the factors that affect agriculture in the tropics. It details the economic and physical factors that affect tropical agriculture and discusses land management and the different types of farming systems in practice. It also discusses tropical crops and the improvements that can be made by effective plant breeding programmes. Information is provided on animal feeds, how animals adapt to their environment and how livestock can be improved by well managed hygiene, breeding and nutrition. The third edition has been fully updated and is an essential reference source for all those requiring a comprehensive introduction to tropical agriculture.
Keywords: Nông nghiệp,Agriculture; Vùng nhiệt đới,Tropics